Analisis Biaya dan Margin Pemasaran Produk Agroindustri Olahan dI Kota Mataram - Suprianto Suprianto; Putu Karismauan; Eka Agustiani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This study aims to determine the marketing patterns of processed agro-industrial products, assess the margins of each marketing agency, the profit description of the institutions and marketing channels, as well as the level of marketing efficiency in each of the marketing channels for processed agro-industrial products in the city of Mataram. This type of research is descriptive using quantitative and qualitative data. Data collection was carried out through interviews with the help of questionnaires. The data analysis used is descriptive analysis using the calculation of marketing margins, profits and efficiency in each marketing agency and marketing channels. The results obtained are the marketing system for processed agro-industrial products in the city of Mataram consists of three marketing channels, namely from producers, collectors, retailers → end consumers. In my marketing channel, skin cracker collectors are traders with a margin of IDR. 15,000 / Kg, while in the marketing channel that has the highest margin in this channel is retail traders, namely IDR 20.000/Kg . Processed bread products with a marketing margin of IDR 250 / pack at retailers, then salted peanut products have a marketing margin of IDR 15,000 / kg in marketing channels I and II, Tofu products and marketing margins of tempe IDR 250 / piece (retailers) and IDR 750 / pack of tempe for traders and IDR 500 / pack for retailers. Processed salted egg products have a marketing margin of IDR 1000 / egg in channel I and IDR 500 / egg in channel II.Marketing efficiency can be seen from the amount of total marketing margin and farmer's share, where in Marketing Channels 1, 2, and 3, it can be seen that all the marketing channels for the processed agro-industrial products are included in the efficient marketing level. The three marketing channels are efficient based on each acquisition of a farmer's share that is above 50 percent. In addition, several factors also underlie these three channels to become an efficient marketing channel, including these factors, namely costs, profits, distance, travel time, marketing facilities and infrastructure. The costs incurred on each of these marketing channels are not very expensive. The costs incurred in each marketing channel consist of transportation costs, labor wages, and packaging costs. The cheaper the costs incurred, the marketing channel can be said to be more efficient and this is in marketing channel II (the average marketing efficiency is 2.1%).